"Medical Doctors Do Not Accept Any Refreshment from Us": Oral History Interviews in a Medical Setting in Sri Lanka. (1st August 2018) - Thoradeniya, Darshi
Abstract: The objective of this article is to share a self-reflective analysis of the oral history interviews that I conducted with attendees of two well-woman clinics in a specific Medical Officer of Health area in Sri Lanka. As a historian and a woman, I trespassed a territorial boundary to conduct research in an area considered to be the exclusive province of medical practitioners and researchers studying public health, community health, and medical sociology. I aimed to understand how women perceived their health beyond a myopic focus on reproductive function. My analysis here deals with the ways in which I deployed oral history practices such as intent listening, deep exchange, self-reflection, consciousness about my position both as an insider and an outsider, consideration of issues related to ethics and exploitation, learning from narrators, and sharing experiences.